2023
DOI: 10.1101/2023.03.01.530713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemically Tunable FOXM1-D Sensor Revealed FOXM1 Direct Influence on Cell Cycle

Abstract: Forkhead box protein M1 (FOXM1) is a proliferation-associated transcription factor contributing to the G2/M phase transition of the cell cycle. Although the upregulation of FOXM1 has been observed in different cancer types, how the regulation of FOXM1 dynamically alters during cell cycles and potentially contributes to tumorigenesis is not well understood. We showed here the development and application of a tunable FOXM1-DHFR (FOXM1-D) sensor that enables surveillance and manipulation of the FOXM1 abundance. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…It isThe copyright holder for this preprint this version posted July 28, 2024. ; https://doi.org/10.1101/2024.07.27.605093 doi: bioRxiv preprint 14 Cells can exhibit varied signaling dynamics (e.g., pulsatile, sustained high, sustained low) in response to the same perturbagen, influencing diverse cell fate decisions(49,50). For example, Phongkitkarun et al, 2023, observed distinct cellular fates single-round or two-round division following TMP administration, linked to FOXM1 signaling dynamics(51). In our study, treatment with Aurora Kinase and PLK1 inhibitors at different doses also revealed heterogeneity in cellular responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It isThe copyright holder for this preprint this version posted July 28, 2024. ; https://doi.org/10.1101/2024.07.27.605093 doi: bioRxiv preprint 14 Cells can exhibit varied signaling dynamics (e.g., pulsatile, sustained high, sustained low) in response to the same perturbagen, influencing diverse cell fate decisions(49,50). For example, Phongkitkarun et al, 2023, observed distinct cellular fates single-round or two-round division following TMP administration, linked to FOXM1 signaling dynamics(51). In our study, treatment with Aurora Kinase and PLK1 inhibitors at different doses also revealed heterogeneity in cellular responses.…”
mentioning
confidence: 99%
“…In our study, treatment with Aurora Kinase and PLK1 inhibitors at different doses also revealed heterogeneity in cellular responses. Aurora Kinase inhibitors induced G2/M arrest and occasional cell death, while PLK1 inhibitors caused cell populations to arrest either in G1 with delayed FOXM1 peak or in G2/M with sustained FOXM1 levels, likely due to delayed FOXM1 degradation(51). The observed heterogeneity in FOXM1 response highlights the importance of considering individual cell behaviors to understand drug efficacy and cellular outcomes.Our study employs a biosensor-based approach to explore FOXM1 dynamics and investigate heterogeneous cellular responses to various cell cycle perturbations.…”
mentioning
confidence: 99%